You can't buy what you can't see: Retailer practices to increase the green premium. (January 2017) - Guyader, Hugo; Ottosson, Mikael; Witell, Lars
Abstract: Retailers are the gatekeepers between consumers and eco-friendly products. As such, they can influence green shopping behavior. The results of an eye-tracking experiment show that retailers can attract consumers' visual attention and increase the green premium through various practices such as providing relevant information, orienting consumers inside the store, and offering an eco-friendly product assortment. Managerial implications are to use green-colored price tags to signal eco-friendly products, while avoiding greenwashing practices that can distract consumers from finding the eco-friendly products they look for.